2003
DOI: 10.1001/jama.289.24.3243
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Estrogen Plus Progestin on Breast Cancer and Mammography in Healthy Postmenopausal Women

Abstract: REAST CANCER IS THE MOST common invasive cancer in US women and its etiology is not fully defined. 1,2 Despite observational studies suggesting increased breast cancer risk with estrogen 3 and especially long-duration combined hormone use, 4,5 the magnitude of breast cancer risk associated with menopausal hormone therapy is controversial. 6,7 On July 9, 2002, the Women's Health Initiative (WHI) reported results from the randomized controlled trial of 16 608 postmenopausal women comparing effects of estrogen pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
410
2
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,639 publications
(435 citation statements)
references
References 47 publications
15
410
2
8
Order By: Relevance
“…9 The Women's Health Initiative Study firmly established that treatment with progestin in combination with estrogen (E2) for attenuating postmenopausal symptoms increases the risk of breast cancer, particularly TNBC. 10 This finding is corroborated to some extent in mice, in which progesterone (P4) promotes 7,12-dimethylbenz[a]anthracene-induced mammary tumors. 11,12 Breast cancer cells and tumors respond to progestins through an unknown mechanism, which generally act as pro-survival and proliferative factors.…”
Section: Introductionmentioning
confidence: 70%
“…9 The Women's Health Initiative Study firmly established that treatment with progestin in combination with estrogen (E2) for attenuating postmenopausal symptoms increases the risk of breast cancer, particularly TNBC. 10 This finding is corroborated to some extent in mice, in which progesterone (P4) promotes 7,12-dimethylbenz[a]anthracene-induced mammary tumors. 11,12 Breast cancer cells and tumors respond to progestins through an unknown mechanism, which generally act as pro-survival and proliferative factors.…”
Section: Introductionmentioning
confidence: 70%
“…by EMEA in December 2003, is largely the consequence of the believe that HRT should increase the risk of breast cancer, mainly deduced again from the first publications of the WHI data [26,27]. However, newer publications from the WHI are showing a quite different picture.…”
Section: Breast Cancer Riskmentioning
confidence: 99%
“…Level I evidence) suggests the MWS probably overestimated the degree of risk attributable to HRT and underestimated the duration of exposure associated with an increase in incidence. [13][14][15] The latter is accounted for in that risk estimates were based on information about duration of HRT use at recruitment only. Adding an average of 1.2 years (i.e.…”
Section: Breast Cancer Incidencementioning
confidence: 99%
“…This evidence has shown that it is probably only combined therapy that results in an increase in mammographic breast density and hence a potential impact on interval cancer rates due to a reduction in sensitivity (increasing the chance of a cancer being missed at a previous screen). 13,15,21 Only about 25% of women who use combined therapy actually develop any density increase and when it occurs it is of the order of about a 5% increase. 21 This effect of combined HRT occurs regardless of the class of progestogen or prescription pattern (i.e.…”
Section: Hrt and Screening Mammographymentioning
confidence: 99%
See 1 more Smart Citation